Frequency and clinical significance of antibodies to ribonucleoprotein in SLE and other connective tissue disease subgroups. Issue 5 (October 1977) - Grennan, D M; Bunn, C; Hughes, G R; Buchanan, W W; Dick, W C
Abstract : Antibodies to the ribonucleoprotein (RNP) component of extractable nuclear antigen were measured in patients with systemic lupus erythematosus (SLE) and other connective tissue subgroups by counterimmunoelectrophoresis. Antibodies to RNP were found in the sera of 32% of patients with a primary diagnosis of SLE, 29% of patients with features of SLE and erosive joint disease, none of 9 scleroderma patients, and in 75% of 8 patients with features of SLE and scleroderma. In the SLE patients overall there was an increased frequency of sclerodactyly and severe Raynaud's phenomenon in the patients with antibodies to RNP but no association of antibodies to RNP was found with the presence of erosive joint disease, Sjögren's syndrome, or the absence of renal disease in these patients.